Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Trả lời
A.12:(x+4).3=6
12:(x+4) =6:3
12:(x+4) =2
x+4 =12:2
x+4 =6
x =6-4
x =2
a) 12 : (x + 4).3 = 6
\(\frac{12}{\left(x+4\right)}.3=6\)
\(\frac{36}{\left(x+4\right)}=6\)
x + 4 = 36 : 6
x + 4 = 6
x = 6 - 4
x = 2
b) 12 : (x + 4).3 = 5
\(\frac{12}{\left(x+4\right)}.3=5\)
\(\frac{36}{\left(x+4\right)}=5\)
x + 4 = 36 : 5
x + 4 = \(\frac{36}{5}\)
x = \(\frac{36}{5}\) - 4
x = \(\frac{16}{5}\)
c) 12 : (x + 4).3 + 18 = 24
\(\frac{12}{\left(x+4\right)}.3+18=24\)
\(\frac{18x+108}{x+4}=24\)
18x + 108 = 24x + 96
18x + 108 - 24x = 96
-6x + 108 = 96
-6x = 96 - 108
-6x = -12
x = -12 : -6
x = 2
18 - 4\(x\) = -20 - 6\(x\)
-4\(x\) + 6\(x\) = - 20 - 18
2\(x\) = - 38
\(x\) = - 19
h, -15 \(\times\) 24 = -7\(x\) + 32
7\(x\) = 360 + 32
7\(x\) = 392
\(x\) = 392:7
\(x\) = 56
i, 15\(x\) -3.(4\(x\) - 6) = -12 + 36
15\(x\) - 12\(x\) + 18 = 24
3\(x\) = 24 - 18
3\(x\) = 6
\(x\) = 2
k, -10\(x\) - 27 = -7\(x\) + 33
-27 - 33 = -7\(x\) + 10\(x\)
3\(x\) = -60
\(x\) = -20
1) 9 . (x + 7) - 12 = 24
9 . (x + 7) = 24 + 12
9 . (x + 7) = 36
x + 7 = 36 : 9
x + 7 = 4
x = 4 - 7
x = -3
2) 12 - 3x = -30
3x = 12 - (-30)
3x = 12 + 30
3x = 42
x = 42 : 3
x = 14
3) 95 - 105 : x = 60
105 : x = 95 - 60
105 : x = 35
x = 105 : 35
x = 3
4) x + 35 = 12
x = 12 - 35
x = -23
5) (-24) - (10 - x) = 43
-24 - 10 + x = 43
-34 + x = 43
x = 43 - (-34)
x = 43 + 34
x = 77
6) 6 - (17 + x) = -16
6 - 17 - x = -16
-11 - x = -16
x = -11 - (-16)
x = -11 + 16
x = 5
7) (x - 18) - (-3) = 0
x - 18 + 3 = 0
x - 18 = 0 - 3
x - 18 = -3
x = -3 + 18
x = 15
8) 25 - (x - 6) = -1
25 - x + 6 = -1
25 - x = -1 - 6
25 - x = -7
x = 25 - (-7)
x = 25 + 7
x = 32
1)9.(x+7)-12=24
9.(x+7)=24+12
9.(x+7)=36
x+7=36:9
x+7=4
x=4-7
x=-3
a)15/8+3/4-5/12
=45+18-10/24
=53/24
b)11/24.12/33+5/6
=11.12/12.2.11.3+5/6
=1/6+5/6
=6/6=1
c)15/8+7/24:5/8
=15/8+7/24.8/5
=15/8+7.8/3.8.5
=15/8+7/15
=đề sai, nếu đúng thì như này
=8/15+7/15
=15/15=1